Attitudes toward Mormons and Voter Behavior in the 2012 Presidential Election. Issue 1 (20th January 2015) - Hawley, George
Abstract: Prior to the 2012 presidential election, some commentators speculated that Mitt Romney's status as a devout and active member of the Church of Jesus Christ of Latter-day Saints would undermine his presidential aspirations. Using the 2012 American National Election Survey, this study examines the relationship between attitudes toward Mormons and voter behavior in the United States in that election year. It finds that attitudes toward Mormons had a statistically-significant effect on turnout — though these effects differed according to party identification. It additionally finds that these attitudes influenced vote choice. In both cases, the substantive effects were small, indicating that anti-Mormon feelings did play a role in the 2012 presidential election, but they did not determine the final outcome.